Management of Human Resource (HR) Empowerment Planning in Schools - D Sunarsi; Z Sukawi; A Khoiri; R Salam; D Ilham (AL-ISHLAH: Jurnal Pendidikan, 2022)
The availability of human resources is the trigger for quality education in addition to the cost factor and educational infrastructure. The purpose of the study was to analyze the management of teacher resource planning in an ideal school through an educational management approach. Qualitative research methods with literature review on sources that can be accounted for and analyzed descriptively and concluded. The results showed that 1) teacher resource planning in schools through planning analysis based on school goals and objectives, 2) planning management using the conceptual Transactional Planning, 3) Evaluation and Monitoring in Planning based on school external goals, and 4) Needs Projection Analysis, Provision of Personnel educators and education using the linkage of demand and supply of teachers. One element of planning management is not fulfilled, it is assumed that the empowerment of teacher resources is not active and less than optimal in the context of developing education in schools.